FOSTERING COMMUNICATION TO AVOID INTERPERSONAL CONFLICT THE FOUNDATION - Rumiati, Sri; Maftuf, Bunyamin; Malihah, Elly; Kurniati, Pat; Subkhan, Muhamad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Communication is very important in every relationship, both individually and in groups. When we want to communicate with other people, we do it effectively in any condition and it takes someone's readiness to receive information or questions from us. By communicating effectively, we can show a positive personality and open ourselves up to always grow and develop towards success together. In organizational communication, communication occurs both formally and informally, but in principle it discusses problems related to the service. In this article explain how to foster good communication in an organization, which aims to avoid an interpersonal conflict.